Age‐related differences in working memory deficits during nicotine withdrawal. (18th March 2013) - Falcone, Mary; Wileyto, E. Paul; Ruparel, Kosha; Gerraty, Raphael T.; LaPrate, Leah; Detre, John A.; Gur, Ruben; Loughead, James; Lerman, Caryn
Abstract Nicotine withdrawal is associated with subtle working memory deficits that predict subsequent relapse. We examined the neural substrates underlying these processes in treatment‐seeking smokers, and explored the moderating influence of age on abstinence‐induced alterations in brain activity and performance. Sixty‐three smokers participated in two blood oxygen level‐dependent (BOLD) functional magnetic resonance imaging scans while performing a visual N‐back task on two separate occasions: smoking as usual and after 24 hours of biochemically confirmed abstinence (order counterbalanced). Abstinence (versus smoking) led to reduced accuracy, slower median correct response time and reduced BOLD signal change in the three a priori regions of interest: medial frontal/cingulate gyrus and right and left dorsolateral prefrontal cortex. Significant age × session effects were found for BOLD signal change in all three regions, as well as for withdrawal and craving; for all measures, abstinence effects were attenuated in smokers aged ≥50 years compared with those <50 years old. These results suggest that abstinence effects on neurocognitive function may be more pronounced for younger smokers, and may indicate a new avenue for research exploring mechanisms underlying age differences in smoking cessation success.